2007
DOI: 10.1016/j.cancergencyto.2006.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic characterization and gene expression profiling of the trastuzumab-resistant breast cancer cell line JIMT-1

Abstract: Resistance to the HER-2 targeting drug trastuzumab is observed clinically, but the lack of suitable experimental models hampers studies of resistance mechanisms. We characterized a HER-2 positive carcinoma cell line (JIMT-1) derived from a 62-year-old breast cancer patient, clinically resistant to trastuzumab. m-FISH revealed a complex hyperdiploid karyotype with numerous marker chromosomes and unbalanced translocations. CGH revealed numerous regions of copy number aberration (CNA). Further analysis by a-CGH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…While limited data exist about the role of CDK4-cyclin D 1 interactions and trastuzumab resistance, these data suggest a role for dual targeting of the HER2 pathway and CDK4/6. Molecular profiling of the JIMT-1 human breast cancer cell line derived from a woman with progressive HER2-amplified disease while receiving trastuzumab did identify a small amplicon on 12q14.1, which contains the CDK4 gene [48]. …”
Section: Discussionmentioning
confidence: 99%
“…While limited data exist about the role of CDK4-cyclin D 1 interactions and trastuzumab resistance, these data suggest a role for dual targeting of the HER2 pathway and CDK4/6. Molecular profiling of the JIMT-1 human breast cancer cell line derived from a woman with progressive HER2-amplified disease while receiving trastuzumab did identify a small amplicon on 12q14.1, which contains the CDK4 gene [48]. …”
Section: Discussionmentioning
confidence: 99%
“…One reported mechanism of trastuzumab resistance in the JIMT-1 cells is the up-regulation of MUC-4 that can result in steric hindrance, thereby physically blocking the binding of trastuzumab to HER2 (22,23). Another interesting study reported that p53 is up-regulated in JIMT-1 cells; although this may provide a mechanism of resistance to trastuzumab, the p53 mutation status was not evaluated (24). Characterization of the p53 mutational status may provide clues to the IPI-504 mechanism of action in JIMT-1 because mutant p53 is a reported Hsp90 client protein (reviewed in refs.…”
Section: Discussionmentioning
confidence: 99%
“…Basal BC cell line JIMT-1 cells are HER2+, trastuzumab-refractory, ER−, and Vimentin+. The de novo resistance of JIMT-1 cell to trastuzumab can be explained by the emergence of trastuzumab-resistance BCSCs due to the dynamic interaction between HER2 and EMT [98,99,100,101,102,103,104]. JIMT-1 cell line is composed of approximately 10% CD44+/CD24− BCSC.…”
Section: Emt Drives Resistance To Trastuzumabmentioning
confidence: 99%